The Effect of Acupressure on Relieving Cancer-Related Fatigue: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 6 (November 2021) - Hsieh, Shu-Hua; Wu, Chia-Rung; Romadlon, Debby Syahru; Hasan, Faizul; Chen, Pin-Yuan; Chiu, Hsiao-Yean
Abstract : Background: Fatigue, a common complaint reported by patients with cancer or in survivorship, has been negatively associated with quality of life, emotional health, and cognitive functions. Acupressure, a traditional Chinese medicine, has been increasingly practiced in clinical and community settings. However, little evidence supports the beneficial effects of acupressure on the reduction of general, physical, and mental fatigue in cancer survivors. Objective: The aim of this study was to examine the effect of acupressure on fatigue in cancer survivors and the moderators of the effect of acupressure on cancer-related fatigue relief. Methods: Databases, namely, PubMed, Embase, CINAHL, and ProQuest, were searched from their inception to July 17, 2020. No language and publication period restrictions were applied. Only randomized controlled trials that examined the effects of acupressure on cancer-related fatigue were included. A random-effects model was used for data analyses. Results: Fourteen articles involving 776 participants with cancers were included. Acupressure considerably alleviated cancer-related general, physical, and mental fatigue ( g = −0.87, −0.87, and −0.37) compared with controls. Increasing female percentage of participants significantly reduced the effects of acupressure on fatigue ( B = −0.01, P < .001). The executor and operation approach as well as treatment period during chemotherapy did not moderate the effects of acupressure on fatigue relief. Conclusion: Acupressure is effective at alleviating cancer-related fatigue. Implications for Practice: Health professionals and patients can use acupressure to alleviate fatigue during and after chemotherapy. Nursing personnel could incorporate acupressure into clinical practice as part of a multimodal approach to alleviating fatigue in cancer survivors.